A Review on Hepatoprotective Activity of Citrus Limetta - Jangid, Hrishabh; Dubey, Chetan; Anchariya, Rahul (Asian Journal of Pharmaceutical Research and Development, 2020)
Hepatic diseases are a major worldwide health problem, with frequently found in developing countries. They are mainly caused by uses of high doses of chemicals and some drugs. There is no effective drug available that stimulates liver function, offer protection to the liver from damage or help to regenerate hepatic cells. There-fore there is urgent need, for effective drugs to replace/add those in current use. Medicinal herbs are significant source of pharmaceutical drugs. Latest trends have shown increasing demand of phytoconstituents from some medicinal herbs and those medicinal herbs have proven hepatoprotective potential. A number of herbal preparations are available in the market. The present review is aimed at compiling data on promising phytochemicals from medicinal plants that have been tested in hepatotoxicity models using modern scientific system. In this century clinical research has confirmed the efficacy of some herbs in the treatment of liver related disease. Hence, this review article contributes to the knowledge of reported indigenous plants, which are prevalent for prevention and treatment of liver disorders.